2022
DOI: 10.18203/2349-2902.isj20220935
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of orthopaedic case presentations at the rivers state university teaching hospital: a ten-year review

Abstract: Background: Pattern of diseases help institutions and governments to know the dominant disease conditions and how to allocate scarce resources. Knowledge of the pattern of orthopedic disease conditions seen and treated in the Rivers State university teaching hospital will help in guiding the repositioning effort of the department/discipline, especially in the light of the new status of the institution as a teaching hospital for teaching, service delivery and research. The aim of this study therefore was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The demographics of common emergency surgical diseases revealed that majority of gunshot injury victims were males. Similar finding has been observed among orthopaedic patients with fractures in our environment [22,23]. Also, relatively more males than females had acute appendicitis.…”
Section: Discussionsupporting
confidence: 89%
“…The demographics of common emergency surgical diseases revealed that majority of gunshot injury victims were males. Similar finding has been observed among orthopaedic patients with fractures in our environment [22,23]. Also, relatively more males than females had acute appendicitis.…”
Section: Discussionsupporting
confidence: 89%